Proposal of Nutritional Standards for the Assessment of the Nutritional Status of Grapevines in Subtropical and Temperate Regions - Rozane, Danilo Eduardo [UNESP]; Toselli, Moreno; Brunetto, Gustavo; Baldi, Elena; Natale, William; Paula, Betania Vahl de; Lima, Juliana Domingues [UNESP]; Medeiros, Fabiana Campos [UNESP]; Ayres, Gustavo; Gobi, Samuel Francisco (MDPI, 2025)
The necessity for nutritional standards to evaluate the nutritional status of grapevines is a critical concern for viticulturists worldwide. This study addressed the lack of multinutrient standards that consider specific genetic and environmental factors by proposing regional standards based on data collected under different growing conditions. Using the compositional nutrient diagnosis (CND) method and multivariate analyses, leaf samples from 585 commercial vineyards in Emilia-Romagna, Italy, and the states of São Paulo and Rio Grande do Sul, Brazil, were evaluated. The results confirmed significant variations in nutritional standards among regions and cultivars, emphasizing the need for regional adjustments in fertilization recommendations. This work proposes critical levels, sufficiency ranges, and nutritional standards that can improve grapevine nutritional assessments, promoting greater precision in fertilization management. The findings reinforce the importance of regional standards, avoiding the use of unsuitable universal recommendations.
Keywords: CND; discriminant analysis; fertilization; leaf abscission; leaf analysis; Vitis labrusca; Vitis vinifera